2008
DOI: 10.1021/ja8007825
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Photocatalytic H2 Evolution on CdS by Loading MoS2 as Cocatalyst under Visible Light Irradiation

Abstract: This communication presents our recent results that the activity of photocatalytic H2 production can be significantly enhanced when a small amount of MoS2 is loaded on CdS as cocatalyst. The MoS2/CdS catalysts show high rate of H2 evolution from photocatalytic re-forming of lactic acid under visible light irradiation. The rate of H2 evolution on CdS is increased by up to 36 times when loaded with only 0.2 wt % of MoS2, and the activity of MoS2/CdS is even higher than those of the CdS photocatalysts loaded with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
1,070
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,800 publications
(1,105 citation statements)
references
References 33 publications
33
1,070
1
1
Order By: Relevance
“…On the contrary, in composite ZnOS‐60, the ZnS is covered by ZnO and photoexcited holes on the ZnS will not be able to contact with the hole scavengers efficiently 52. The high photocatalytic activity of ZnOS‐30 in comparison with other ZnOS‐n ( n = 15, 45, and 60) may result from the abundant coupling interface between ZnO and ZnS nanoparticles, which improves interfacial charge transfer and therefore effective charge separation 53, 54. In addition, the HER catalytic results match well with the intensities of photocurrent of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, in composite ZnOS‐60, the ZnS is covered by ZnO and photoexcited holes on the ZnS will not be able to contact with the hole scavengers efficiently 52. The high photocatalytic activity of ZnOS‐30 in comparison with other ZnOS‐n ( n = 15, 45, and 60) may result from the abundant coupling interface between ZnO and ZnS nanoparticles, which improves interfacial charge transfer and therefore effective charge separation 53, 54. In addition, the HER catalytic results match well with the intensities of photocurrent of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al first reported that the activity of producing H 2 for 0.2 wt% MoS 2 /CdS was enhanced 36 times compared to pristine CdS, which was even higher than 0.2 wt% Pt/CdS under the same reaction conditions [21][22]. Following this work, MoS 2 /CdS nanocomposites with different physical dimensions have been constructed and applied to HER [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 92%
“…The design strategy requires that the new generation catalysts should prolong the lifetime of the photo-generated charge carriers to elevate their participation in photocatalytic activity (PCA). For such designs, use of heterostructures is an ideal option, where an electron reservoir from a noble metal 2,7-9 or another semiconductor (heterojunction) 5,14,15 is brought into contact. The former case is exploited in core-shell 7,8,11 and nanocomposite 2,9,10 formats, in which the photo-electrons from the conduction band (CB) of the semiconductor are transferred to the noble metal and then to the catalysis process, while the holes react from the valance band (VB) of the semiconductor.…”
Section: Introductionmentioning
confidence: 99%